Acute onset pulmonary toxicity associated to amiodarone - Ferreira, PG (2012)
Amiodarone is a potent anti-arrhythmic drug with a well-known potential chronic pulmonary toxicity. We describe a case of acute pulmonary toxicity (APT) induced by amiodarone in a 57 year old patient submitted to a perfusion of 900 mg in just 6 hours, to control an auricular flutter with rapid ventricular response. During the administration, the patient developed hemodynamic instability and oxygen dessaturation that led to an electrical cardioversion with return of sinus rhythm. Still, the patient continued in progressive respiratory deterioration with acute bilateral infiltrates on chest x-ray and apparent normal cardiac filling pressures confirmed by echocardiography. Anon-cardiogenic pulmonar edema progressing to clinico-physiological ARDS criteria was diagnosed. Expeditive therapeutic measures were undertaken, namely by initiation of non-invasive positive airway pressure support, that attained a good result.Albeit rare, amiodarone-induced APT might have severe consequences, namely progression to ALI/ARDS with a high mortality index.As it is a frequently prescribed drug, there should be a high clinical suspicion towards this phenomenon, allowing precocious therapeutic measures to be taken in a timely fashion to prevent the associated unfavorable outcome.